Activity of Sulbactam-Durlobactam and Comparators Against a National Collection of Carbapenem-Resistant Acinetobacter baumannii Isolates From Greece - Petropoulou, Dimitra; Siopi, Maria; Vourli, Sophia; Pournaras, Spyros (Frontiers in Cellular and Infection Microbiology, 2022)
Background Acinetobacter baumannii is a leading cause of healthcare-associated infections worldwide, due to both its persistence in the hospital setting and ability to acquire high levels of antibiotic resistance. Carbapenem-resistant A. baumannii isolates (CRAB) limit the activity of current antimicrobial regimens and new alternatives or adjuncts to traditional antibiotics are urgently needed. Durlobactam is a novel broad-spectrum inhibitor of serine-type β-lactamases that restores sulbactam (SUL) activity against A. baumannii. The sulbactam-durlobactam (SD) combination has recently completed Phase 3 testing in the global ATTACK trial. Objectives The aim of this study is to evaluate the in vitro activity of SD versus comparators against a representative nationwide collection of CRAB isolates. Methods One hundred ninety CRAB isolates were collected from clinical samples of patients hospitalized in 11 hospitals throughout Greece during 2015. In vitro activities of SD and comparators (SUL alone, amikacin, minocycline, imipenem, meropenem, colistin, SD and imipenem combined with SD) were determined by broth microdilution. Results Durlobactam restored sulbactam activity against the majority of the strains tested, with SD exhibiting the lowest MIC90 (8 μg/ml) relative to the other single comparators tested; 87.9% of the isolates had SD MICs ≤4/4 µg/ml. The most active comparator was colistin (MIC90 = 16 μg/ml). The addition of imipenem further lowered the MIC90 of SD by one two-fold dilution. Conclusions This study demonstrated the potential utility of SD for the treatment of infections caused by A. baumannii. If its clinical efficacy is confirmed, SD may be an important therapeutic option for CRAB infections.